1982
DOI: 10.1161/01.cir.66.3.665
|View full text |Cite
|
Sign up to set email alerts
|

The tricuspid valve annulus: study of size and motion in normal subjects and in patients with tricuspid regurgitation.

Abstract: SUMMARY The tricuspid valve leaflets and their annular attachments were recorded by two-dimensional echocardiography from a view of the right ventricular inflow tract obtained by placing the transducer at an intermediate position between the left ventricular apex and the left lower sternal border. The transducer was rotated, and recordings were made at 300 rotational intervals around the circumference of the tricuspid valve annulus. The cyclical pattern of variations in tricuspid annular size was studied with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
84
0
3

Year Published

1985
1985
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(100 citation statements)
references
References 16 publications
(5 reference statements)
9
84
0
3
Order By: Relevance
“…In a detailed two-dimensional echocardiographic study by Tei et al, the dynamic, geometric changes of the TA during the cardiac cycle have been demonstrated. 8) They were 19% of the circumference and 33% of the cross-sectional area in normal human subjects, and 10% and 18% in patients with fTR.…”
Section: Methodology Of Tricuspid Valve Surgerymentioning
confidence: 90%
“…In a detailed two-dimensional echocardiographic study by Tei et al, the dynamic, geometric changes of the TA during the cardiac cycle have been demonstrated. 8) They were 19% of the circumference and 33% of the cross-sectional area in normal human subjects, and 10% and 18% in patients with fTR.…”
Section: Methodology Of Tricuspid Valve Surgerymentioning
confidence: 90%
“…Pathological tricuspid regurgitation (TR) is usually functional owing to annular dilatation, which may arise because of LV failure, RV pressure and/or volume overload, or chamber dilatation. The tricuspid valve (TV) annulus is very dynamic and changes markedly with different loading conditions; even during the normal cardiac cycle, there is a 30% reduction in annular area in atrial systole [56]. This means that the degree of TR is very variable and heavily dependent on intravascular volume status, RV loading and RV function.…”
Section: Right-sided Valvular Heart Diseasementioning
confidence: 99%
“…The normal valve area is 7.6 ± 1.4 cm. 2,4 Anatomically, the tricuspid valve is closely related to the coronary sinus, atrioventricular nodal conduction tissue and the right coronary artery.…”
Section: Tricuspid Diseasementioning
confidence: 99%